2015
DOI: 10.1101/gad.259432.115
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions of centromeric chromatin regulate the cell cycle-dependent recruitment of CENP-N

Abstract: Specific recognition of centromere-specific histone variant CENP-A-containing chromatin by CENP-N is an essential process in the assembly of the kinetochore complex at centromeres prior to mammalian cell division. However, the mechanisms of CENP-N recruitment to centromeres/kinetochores remain unknown. Here, we show that a CENP-A-specific RG loop (Arg80/Gly81) plays an essential and dual regulatory role in this process. The RG loop assists the formation of a compact "ladder-like" structure of CENP-A chromatin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 61 publications
10
75
0
Order By: Relevance
“…The CENP-N N-terminal region (residues 1 to 286 in humans) is responsible for recognition of the CENP-A nucleosome (7, 8), whereas its C-terminal region (residues 287 to 339) interacts with the CCAN through CENP-L (9, 10). The recruitment of CENP-N to the centromere requires recognition of the L1 loop of CENP-A (11). …”
mentioning
confidence: 99%
“…The CENP-N N-terminal region (residues 1 to 286 in humans) is responsible for recognition of the CENP-A nucleosome (7, 8), whereas its C-terminal region (residues 287 to 339) interacts with the CCAN through CENP-L (9, 10). The recruitment of CENP-N to the centromere requires recognition of the L1 loop of CENP-A (11). …”
mentioning
confidence: 99%
“…This situation creates separate hierarchies during de novo CCAN recruitment and for maintenance of CCAN components at various cell cycle stages. CENP-C and CENP-N bind directly to CENP-A nucleosomes in vitro (Carroll et al 2009(Carroll et al , 2010Kato et al 2013;Falk et al 2015Falk et al , 2016Fang et al 2015) and localize near the CENP-A chromatin in vivo (Fig. 3a) (Wan et al 2009).…”
Section: Cenp-c Functions Upstream Of Other Ccan Components During Dementioning
confidence: 93%
“…Recent studies suggest that there is no clear hierarchy for CCAN recruitment and maintenance (Hori et al 2008a;Fang et al 2015;McKinley et al 2015;Nagpal et al 2015), although there are active debates about this issue (Carroll et al 2010;Basilico et al 2014;Klare et al 2015). Various dynamic interactions between the different CCAN sub-complexes result in an extensive meshwork of interactions ( Fig.…”
Section: Cenp-c Functions Upstream Of Other Ccan Components During Dementioning
confidence: 97%
“…By using biochemical, biophysical, and cell-based assays, we showed that the RG loop, the two CENP-A-specific residues Arg80 and Gly81 in loop1 located at the lateral surface of CENP-A nucleosome (Tachiwana et al 2011), not only provides the recognition site for the binding of CENP-N to the CENP-A nucleosome, but also facilitates the folding of CENP-A arrays into a compact "ladder-like" chromatin structure in the presence of MgCl 2 , as revealed by AUC and EM analyses ( Fig. 5A-C ;Fang et al 2015). Interestingly, we found that the formation of a compact "ladder-like" structure of CENP-A chromatin inhibits the binding and recruitment of CENP-N through concealing/hiding the RG loop within chromatin fiber.…”
Section: Epigenetic Regulation Of Chromatin Fibers By Chromatin Factorsmentioning
confidence: 97%